Expression of CIB1 correlates with colorectal liver metastases but not with peritoneal carcinomatosis - Sven Jacob (BMC, 2021)
Abstract Background Molecular differences in colorectal cancer (CRC) are associated with the metastatic route. Patient survival is mainly driven by metastatic spread thus it is imperative to understand its key drivers to develop biomarkers for risk stratification, follow-up protocols and personalized therapy. Thus, this study aimed to identify genes associated with the metastatic route in CRC. Material and methods CRC patients resected at our clinic from 2005 to 2014 and with a minimum 5-year follow-up were included in this analysis and grouped into CRC with hepatic (HEP), peritoneal (PER) or without distant metastases (M0), and HEP/PER. Firstly, tumor RNA of 6 patients each was isolated by microdissection from formalin-fixed paraffin-embedded specimens and analyzed by a NanoString analysis. Subsequently, these results were validated with immunohistochemistry and correlated to clinicopathological parameters in a larger collective of CRC patients (HEP n = 51, PER n = 44, M0 n = 47, HEP/PER n = 28). Results Compared to M0, HEP tumors showed 20 differentially expressed genes associated with epithelial-mesenchymal transition (EMT) and angiogenesis. Compared to M0, PER tumors had 18 differentially expressed genes. The finding of different gene signatures was supported by the multidimensional principal component clustering analysis. Tumor perforation did not influence the metastatic route. CIB1 was homogenously and significantly overexpressed in HEP compared to M0 (p < 0.001), but not in PER. Furthermore, immunohistochemical validation demonstrated that the mean CIB1 expression in HEP was 80% higher than in M0 (p < 0.001). Conclusion Gene expression analysis revealed that CIB1 is significantly overexpressed in CRC leading to liver metastases compared to M0 and PER. Thus, the present results suggest that CIB1 may play a crucial role for hematogenous spread to the liver but not for peritoneal carcinomatosis. Consequently, CIB1 seems to be a promising prognostic marker and a potential tool for future targeted therapies as well as early diagnostics and follow-up.